Post-infectious bronchiolitis obliterans and subpleural cysts in a 30-month-old boy with down syndrome - Nurdiyana N,; Faizah MZ,; Hasniah Abdul Latif, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Post-infectious bronchiolitis obliterans is a rare disease that may occur following a microbiological insult towards the lower respiratory tract causing a severe form of chronic obstructive airway disease. Subpleural lung cyst may occur in 20-36% of Down syndrome. We report a case of a 30-month-old Down syndrome child who had interesting radiological concurrent findings of bronchiolitis obliterans with subpleural cysts on High Resolution Computed Tomography (HRCT) thorax. This patient was born premature and had early onset pneumonia during the neonatal period. Subsequently, he had three episodes of pneumonias at 18, 19 and 26 months. He presented with recurrent symptoms of cough, wheeze, rapid breathing and had features of persistent airway obstruction characterized by chest hyperinflation, persistent tachypnoea with crepitations and rhonchi despite on regular bronchodilators. The only positive culture was Influenza B from his nasopharyneal aspirate culture. To our knowledge, this is the first reported case with both radiological entities in a child with Down syndrome.